Development of Dengue Hemorrhagic Fever Prevention and Control Model in Samut Sakhon Province Using Community Participation - Maneeprasirt, Siriluk (Journal of Health Science of Thailand, 2017)
The objectives of this study were to review the implementation of dengue hemorrhagic fever (DHF) prevention and control program in Samut Sakorn province and to develop a community participa-tion model in the program using participatory action research. It was conducted in 2 steps: a situation survey and a participatory action research (PAR). The survey was conducted in 40 sub-districts in Samut Sakorn province by reviewing disease surveillance reports. Descriptive statistics were used to analyze the data. As for the PAR, it was carried out in 6 subdistructs which were the top-two highest DHF prevalence sub-districts of each of the three districts of the province. The activities included a workshop to develop a DHF prevention and control model using community participation. Activities in this workshop consisted of health education to provide information about DHF prevention and control and brainstorming for model development. The participants in this workshop were purposively selected from those who involved in DHF prevention and control programs, consisting of local administration organization officers, public health staff, village headman, community leaders, village health volunteers (VHVs), and representatives of families whose members had experienced DHF. The total number of the participants was 60, who implemented the model in their respective areas for one year. The evaluation was carried out using obser-vation, in-depth interview, and document reviews. The output indicators used in the evaluation were DHF incidence, second generation DHF cases, and larva index. Results from the initial survey showed that the DHF incidence of the province exceeded the minimum standard and the incidence of second generation DHF was 57.7%. The house index (HI) was 8.59 which was close to the standard value; and the container index (CI) was 5.69, which was higher than the standard criterion. Most DHF prevention and control activities were executed by government sectors. Weaknesses of the project implementation included inad-equate coordination and unclear functions and roles of stakeholders resulting in hindrances of resource support. In addition, the inefficient dissemination of the outbreak and lack of community participation causing unsustainable program and certain areas were left out. These weaknesses were discussed in the workshop and recommendations for improvement were made accordingly as follow. Each sub-district set up a DHF prevention and control committee with clearly defined functions and roles of each party in-volved. Knowledge on disease surveillance was enhanced among the partners, before and after the out-breaks. Other activities included mapping of a concrete plan for effectively and continuously providing health education to the public, and using community participatory social measures to move the program forward. The evaluation of the model showed that the larva index (HI and CI) of all six sub-districts were under the standard criterion. The incidence of DHF was reduced and the second generation DHF cases was not detected. Therefore, it is recommended that this DHF prevention and control model should be applied in other areas.